2020
DOI: 10.3389/fmicb.2020.560102
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Different Size Phytoplankton for Primary Production and Biochemical Compositions in the Western East/Japan Sea

Abstract: The current phytoplankton community structure is expected to change, with small phytoplankton becoming dominant under ongoing warming conditions. To understand and evaluate the ecological roles of small phytoplankton in terms of food quantity and quality, the carbon uptake rates and intracellular biochemical compositions (i.e., carbohydrates, CHO; proteins, PRT; and lipids, LIP) of phytoplankton of different sizes were analyzed and compared in two different regions of the western East/Japan Sea (EJS): the Ulle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 75 publications
(156 reference statements)
1
19
0
Order By: Relevance
“…In this study, the negative relationship between the nano-sized phytoplankton contribution and the primary production indicates that increasing contributions of the nano-sized phytoplankton could decrease the primary production in the YS. In the EJS, several previous studies reported higher contributions of pico-sized phytoplankton could cause a decrease in the primary production [12,22,69]. Indeed, marked decreasing trends in the primary productions with increasing pico-sized phytoplankton biomass were observed in the SS and EJS during our observation period in 2018 (Figure 9b.c).…”
Section: Comparisons Of Primary Production Between This and Previous Studiessupporting
confidence: 62%
See 3 more Smart Citations
“…In this study, the negative relationship between the nano-sized phytoplankton contribution and the primary production indicates that increasing contributions of the nano-sized phytoplankton could decrease the primary production in the YS. In the EJS, several previous studies reported higher contributions of pico-sized phytoplankton could cause a decrease in the primary production [12,22,69]. Indeed, marked decreasing trends in the primary productions with increasing pico-sized phytoplankton biomass were observed in the SS and EJS during our observation period in 2018 (Figure 9b.c).…”
Section: Comparisons Of Primary Production Between This and Previous Studiessupporting
confidence: 62%
“…Lee et al [8,9] also reported that an algorithm for estimation of the habitat suitability index for the mackerels and squids around the Korean peninsula was largely improved by including a primary production term. The physiological conditions and community structures of phytoplankton are closely related to physical and chemical factors (e.g., light regime, nutrients, and temperature) [10][11][12], which induce greatly different phytoplankton productions in various marine ecosystems [3,13,14]. Thus, the primary production measurements can provide fundamental backgrounds for better understanding marine ecosystems with different environmental conditions and detecting current potential ecosystem changes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Normally, the primary production by picophytoplankton (i.e., picocyanobacteria and picoeukaryotes) is estimated through filter fractionation [7,[27][28][29][30][31]. However, it is difficult to distinguish carbon and/or nitrogen uptake rates between picocyanobacteria (Prochlorococcus and Synechococcus) and picoeukaryotes.…”
Section: Introductionmentioning
confidence: 99%